Impact of hepatitis C virus clearance by direct-acting antiviral treatment on the incidence of major cardiovascular events: A prospective multicentre study. (March 2020) - Adinolfi, Luigi Elio; Petta, Salvatore; Fracanzani, Anna Ludovica; Coppola, Carmine; Narciso, Vincenzo; Nevola, Riccardo; Rinaldi, Luca; Calvaruso, Vincenza; Staiano, Laura; Di Marco, Vito; Marrone, Aldo; Pafundi, Pia Clara; et al.
Abstract: Background and aims: HCV is associated with an increased risk of cardiovascular events (CV). Whether HCV clearance by direct-acting antivirals (DAA) reduces incident CV disease is poorly understood. We investigate whether HCV eradication reduces CV events. Methods: In a prospective multicentre study, 2204 HCV patients (F0–F2:29.5%, F3–F4: 70.5%) were enrolled. Males were 48%, median age was 68 (59–74) years and BMI 25.9 (23.1–28); 24.7% were smokers, 18% had diabetes, 13.2% had cholesterol levels >200 mg/dl and 9.1% took statins, 44% had hypertension. During an overall median follow-up of 28 (24–39) months, incident CV events, such as ischemic heart disease (IHD) and ischemic cerebral stroke (ICS), were recorded. An overall of 2204 patients were evaluated as control group and 1668 patients after HCV elimination were followed as a case group. Factors associated with CV events were evaluated by uni- and multi-variate analyses. Results: Incident CV rates per 100 patient years in pre-treatment and untreated controls and treated cases were 1.12, 1.14 and 0.44 ( p = 0.0001 vs. controls), respectively, and a decreased of relative risk (RR = 0.379; p = 0.0002) was observed. CV risk was 2.0–3.5 times lower then in controls (HR 3.671; 95%C.I.:1.871–7.201; p < 0.001). The calculated number of patients to be treated to get a benefit in a patient was 55.26. The annual incidence reduction of CV events was 0.68%. HCV clearance was independently associated with CV events reduction (OR, 4.716; 95% C.I.:1.832–12.138; p = 0.001). Conclusions: HCV clearance by DAA reduces CV events (IHD and ICS) with both clinical and socio-economic benefits. Highlights: HCV clearance by direct-acting antivirals (DAA) significantly reduces the annual incidence of cardio vascular events by 0.68%. Incident cardiovascular events (CV) rates for 100 patient years in controls was 1.14 and in cases 0.44. The CV risk after HCV clearance was reduced by 2.0–3.5 folds. The calculated number of patients to be treated to get a benefit in a patient was 55.26. HCV clearance was independently associated with CV events reduction.